إشكالية الهوية في المجتمعات المعاصرة: مقاربة نفسية ثقافية - العقون, لحسن; جارالله, سليمان (دفـاتر المـــــــــــخبـر; No 19 (2018): مجلة دفاتر, 2018)
إذا كانت مسألة الهوية قد طفت إلى السطح في العالم العربي المعاصر (منها الجزائر) فهذا نابع من وضعيات الصراع والتعدد الثقافي التي فرضتها كلا من الحركة الاستعمارية والهجرة والعولمة، إضافة إلى إخفاق السياسات الثقافية المتبعة في العقود الماضية في استيعاب قيم وعناصر الحضارة الحديثة. الشيء الذي خلق مجتمعات يعايش الفرد فيها نماذج ثقافية متعددة في آن واحد، مما يجعله يعيش ثقافته بشكل صراعي تتجاذبه الحداثة بمقابل إلزامية الحفاظ على الثقافة المحلية وشرعة الإسلاف. إن كل ثقافة تعتمد على التناسق بين الفرد الاجتماعي ومحيطه الخارجي في عملية انتقالها من جيل إلى آخر، وهذا بالتركيز على الوظيفة الانطولوجية، لكن قد نجد عكس ذلك بالتركيز الوظيفة البراغماتية بقوة في فترات التحول والتفاعل الثقافي مع ثقافات وافدة لأن الفرد في هذه الفترة تظهر لديه في كل لحظة أزمة معنى مما يدفعه إلى اللجوء إلى مجموعة من الاستراتيجيات النفسية الجماعية للتوفيق بين هذه المعايير الثقافية المتضادة، وتساعده في اكتساب هوية ديناميكية قادرة على التغير The issue of identity has emerged in the contemporary Arab world (notably in Algeria), which stems from situations of conflict and cultural diversity imposed by both the colonial movement, immigration and globalization, in addition to failure cultural policies established in recent decades to assimilate the values ​​and elements of modern civilization. Which creates communities in which the individual experiences several cultural models at the same time, which enables him to live his culture in an intercultural way, in which he wants to modernize in the face of the obligation to preserve the local culture with these values ​​and the traditional norms of society. Each culture depends on the harmony between the social individual and the external environment in the process of transgenerational transmission, and this by the process of socialization by focusing on the ontological system. However, we can find the opposite strongly based on the pragmatic function in periods of cultural transformation and interaction with foreign cultures, because the individual in this period seems to have a crisis of meaning at any moment. This leads him to resort to a set of psychological strategies to reconcile these conflicting cultural norms and help him to acquire a dynamic identity.. المستمر